A Proposed IoT-Enabled Smart Waste Bin Management System and Efficient Route Selection. (16th December 2019) - Zeb, Asim; Ali, Qurban; Saleem, Muhammad Qaiser; Awan, Khalid Mahmood; Alowayr, Ali Saeed; Uddin, Jamal; Iqbal, Saleem; Bashir, Faisal
Abstract : Internet of Things (IoT) is an emerging technology that offers promising solutions to modernize the traditional systems. It accords promising result in crystallizing smart cities, smart homes, smart industries, and smart environment. This article presents the smart waste management architecture for smart cities and efficient routing technique considering least delay for the architecture. In wireless sensor networks, end-to-end delay is one of the important Quality of Services (QoS) parameter to overcome delay in data communication. In this article, we consider end-to-end delay minimization in smart waste management application. The term "end-to-end delay" is defined as the total time taken by a single packet to reach the destination node. The proposed scheme considers the interference level, the length of the routing path, and the number of hops along the path. The simulation results show that the proposed scheme outperforms current schemes.